Chapter 35 Differentiation at the local level An overview of subnational authority networks in the EU - Tortola, Pier Domenico (Taylor & Francis, 2022)
Transnational networks of sub-national authorities are an established and growing phenomenon in Europe, where they perform a number of (soft) governance functions for their membership, often in direct connection with European Union institions. This chapter examines networks from the angle of institutional differentiation - an inherent trait of these organisations - in order to expand the analysis of this phenomenon beyond its state-centric confines. The chapter also adds to the study of (differentiated) integration more traditionally defined, both by analogy and insofar as networks are part and parcel of the EU's system of multi-level governance. Building on original empirical data, we identify three dimensions of differentiation generated by networks - "insider-outsider", "compound", and "multi-level" differentiation - and discuss their implications for the efficiency, effectiveness and legitimacy of networks' actions. Based on our analysis, we also sketch some avenues for future research connecting the national and sub-national dimensions of differentiation in Europe.